2014
DOI: 10.1371/journal.ppat.1004251
|View full text |Cite
|
Sign up to set email alerts
|

T-bet and Eomes Are Differentially Linked to the Exhausted Phenotype of CD8+ T Cells in HIV Infection

Abstract: CD8+ T cell exhaustion represents a major hallmark of chronic HIV infection. Two key transcription factors governing CD8+ T cell differentiation, T-bet and Eomesodermin (Eomes), have previously been shown in mice to differentially regulate T cell exhaustion in part through direct modulation of PD-1. Here, we examined the relationship between these transcription factors and the expression of several inhibitory receptors (PD-1, CD160, and 2B4), functional characteristics and memory differentiation of CD8+ T cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
307
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 256 publications
(330 citation statements)
references
References 67 publications
(100 reference statements)
22
307
1
Order By: Relevance
“…Our results also demonstrate that PD-1 levels are increased among CD27 + CD8 + T cells in HIV-TB patients, providing new evidence pointing to an exhausted phenotype restricted to those cells that home to lymph nodes. These results are in line with the association of PD1 expression to a T-bet low /Eomes hi transitional memory phenotype in CD8 + T cells from HIV + patients observed by Buggert et al [31]. Strikingly, our observation of a positive correlation between PD-1 expression on CD27 + CD8 + T cells (a population that includes T N , T CM , and transitional memory cells) and % CD45RA dim cells in T TE points to an arrest of exhausted cells on less functional phenotypes as observed in HIV + patients [31].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our results also demonstrate that PD-1 levels are increased among CD27 + CD8 + T cells in HIV-TB patients, providing new evidence pointing to an exhausted phenotype restricted to those cells that home to lymph nodes. These results are in line with the association of PD1 expression to a T-bet low /Eomes hi transitional memory phenotype in CD8 + T cells from HIV + patients observed by Buggert et al [31]. Strikingly, our observation of a positive correlation between PD-1 expression on CD27 + CD8 + T cells (a population that includes T N , T CM , and transitional memory cells) and % CD45RA dim cells in T TE points to an arrest of exhausted cells on less functional phenotypes as observed in HIV + patients [31].…”
Section: Discussionsupporting
confidence: 92%
“…These results are in line with the association of PD1 expression to a T-bet low /Eomes hi transitional memory phenotype in CD8 + T cells from HIV + patients observed by Buggert et al [31]. Strikingly, our observation of a positive correlation between PD-1 expression on CD27 + CD8 + T cells (a population that includes T N , T CM , and transitional memory cells) and % CD45RA dim cells in T TE points to an arrest of exhausted cells on less functional phenotypes as observed in HIV + patients [31]. Several authors have explored the dynamics of Mtb-specific CD4 + T cells but just a few studies have been focused on Mtbspecific CD8 + T cells.…”
supporting
confidence: 77%
See 1 more Smart Citation
“…We and others have recently shown that T-bet and Eomes expression varies in human CD8 ϩ T-cell subsets and virus-specific populations (6,(25)(26)(27)(28). Furthermore, their expression levels were also shown to distinctly correspond to the expression of IL-7R␣, granzymes, and various coinhibitory receptors expressed by exhausted CD8 ϩ T cells (26,27,29). Here, we show that the T-bet and Eomes expression state of an individual CD8 ϩ T-cell corresponds to specific functional traits in a manner that is irrespective of the differentiation status defined by the CD45RA/CCR7/CD28/CD27 subdivision.…”
Section: T He Process Of Viral and Host Coevolvement Has Selected Formentioning
confidence: 92%
“…Statistical analyses were performed using Mann-Whitney U tests. mans (32,33). The high predepletion levels of T-bet expression in SIV-infected progressors may reflect the high levels of activation and antigenic load which resulted from the poor control of virus occurring in progressors.…”
Section: Fig 5 Cd8mentioning
confidence: 99%